2006
DOI: 10.1088/0268-1242/21/5/020
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and band offset of type-II AlGaAsSb/InP heterostructures

Abstract: The optical properties of lattice-matched InP/Al x Ga 1−x AsSb layers for 0 x 0.17 have been investigated by photoluminescence (PL) spectroscopy at 15 K. The PL revealed emission peaks corresponding to the band-to-band transitions of AlGaAsSb and InP. Moreover, a second emission due to the spatially indirect recombination (type-II) of electrons in the conduction band (CB) of InP and holes in the valence band (VB) of AlGaAsSb was also observed. The CB and VB offsets between InP and AlGaAsSb are determined for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…AlAs x Sb 1−x is a versatile large-gap barrier material that can be lattice matched to InP, InAs, or GaSb substrates [8,[17][18][19]. The studied ternary alloys (Ga,Al)(As,Sb) form a border of the Al x Ga 1−x As y Sb 1−y quaternary alloys which are interesting materials in the commercial technologies [20].…”
Section: Introductionmentioning
confidence: 99%
“…AlAs x Sb 1−x is a versatile large-gap barrier material that can be lattice matched to InP, InAs, or GaSb substrates [8,[17][18][19]. The studied ternary alloys (Ga,Al)(As,Sb) form a border of the Al x Ga 1−x As y Sb 1−y quaternary alloys which are interesting materials in the commercial technologies [20].…”
Section: Introductionmentioning
confidence: 99%
“…The determination of the VBO by measuring the type II PL emission is a very easy and precise method. Ostinelli et al calculated in their work the VBO between InP and AlGaAsSb-alloys of various compositions using the type II transition 24 and come to a similar degree of precision for the VBO of these materials. Since the measurement of the PL with very high resolution is comparably easy, the main sources of error for the VBO determination lie in the evaluation of the PL shift.…”
Section: Fig 4: (Color Online)mentioning
confidence: 82%
“…Mostly, this method has been used on multi quantum wells made of the In-Al-As-Ga-Sb materials. [23][24][25] In this work, we present a combined theoretical and experimental approach to determine the VBO between CdSe and ZnTe and compare the calculations with the experimentally determined value. The theoretical part presents a refined approach for the calculation of the VBO.…”
Section: Introductionmentioning
confidence: 99%
“…4, dash-dotted lines CB Z and VB Z ). Both the approaches mentioned above are in some conflict with experimental data obtained for the conduction band discontinuity at the type II GaSb 0.5 As 0.5 /InP heterointerface [5,18], because it was found that the discontinuity in the conduction band was about 0.1-0.12 eV, which corresponds to an electron affinity w GaAsSb ¼ À4.27 eV. This is a well lattice-matched heterostructure and the influence of strain-induced effects can be disregarded.…”
Section: Article In Pressmentioning
confidence: 82%